Gen Z's Perception of the Interpersonal Communication Behavior of Guidance and Counseling Teachers That Can Build Rapport - Yuttami Keila Azahra; Moch Johan Pratama (Journal of Psychological Perspective, 2026)
The research is based on the problem of negative perceptions of students who consider BK teachers as "school police" and lack of student trust. This study examines the important role of interpersonal communication of Guidance and Counseling teachers in building rapport with generation Z students. The method used is a qualitative survey with a non-probability sampling technique, the study involved 163 high school students in Bandar Lampung through voluntary sampling. Data were collected through online questionnaires and FGDs about the comfort of interacting with BK teachers and analyzed using thematic analysis with ATLAS.ti 9 software. The results of the study identified two themes in communication behavior that build rapport: care (12 codes) and immediacy (10 codes) and It was found that the communication behavior of guidance and counseling teachers that can build rapport with generation Z students can start with the ability to be fair as the most important top priority., followed by the ability to tell stories with humor to lighten the atmosphere, guidance and counseling teachers can begin to change negative perceptions and build a more positive rapport relationship with students, thereby increasing student trust in guidance and counseling teachers so that students will feel safer, more comfortable and confident in consulting with guidance and counseling teachers. These findings can be used as a reference in the development of interpersonal communication training programs in universities for prospective guidance and counseling teachers, as well as practical guidelines for improving the quality of guidance and counseling services in schools. This study provides an in-depth understanding of the communication behaviors expected by Generation Z for guidance and counseling teachers in increasing the effectiveness of guidance and counseling services.